Antigen Exposure History Defines CD8 T Cell Dynamics and Protection during Localized Pulmonary Infections - Van Braeckel-Budimir, Natalija; Martin, Matthew D.; Hartwig, Stacey M.; Legge, Kevin L.; Badovinac, Vladimir P.; Harty, John T. (Frontiers in Immunology, 2017)
Unlike systemic infections, little is known about the role of repeated localized infections on (re)shaping pathogen-specific memory CD8 T cell responses. Here, we used primary (1°) and secondary (2°) intranasal influenza virus infections of mice as a model to study intrinsic memory CD8 T cell properties. We show that secondary antigen exposure, relative to a single infection, generates memory CD8 T cell responses of superior magnitude in multiple tissue compartments including blood, spleen, draining lymph nodes and lung. Unexpectedly, regardless of the significantly higher number of 2° memory CD8 T cells, similar degree of protection against pulmonary challenge was observed in both groups of mice containing 1° or 2° memory CD8 T cells. Mechanistically, using Pertussis toxin-induced migration block, we showed that superior antigen-driven proliferation and ability to relocate to the site of infection allowed 1° memory CD8 T cells to accumulate in the infected lung during the first few days after challenge, compensating for the initially lower cell numbers. Taken together, the history of antigen exposures to localized pulmonary infections, through altering basic cell biology, dictates dynamic properties of protective memory CD8 T cells responses. This knowledge has important implications for a design of novel and an improvement of existing vaccines and immunization strategies.